Perang Salib: Dampaknya Terhadap Peradaban Islam dan Kristen di Abad Pertengahan - N, Nurfadilah; Mauduto, Maryam; Sulaiman, Umar (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
The Crusades were a series of military conflicts involving European Christian powers and the Islamic world in the Middle East during the 11th to 13th centuries. These conflicts had impacts far beyond the military realm, affecting various aspects of civilization, including politics, society, economy, and culture in both hemispheres. For Islamic civilization, the Crusades accelerated the process of political consolidation and spurred the development of more organized military strategies, as well as encouraging increased mobilization of resources to defend their territories. In contrast, for Europe, the Crusades contributed to economic transformation by opening new trade routes, intellectual influence through contact with the Islamic world, and changes in social and political structures that strengthened the power of the church and kingdom. This study highlights the impact of the mutual influence between the two civilizations and explains how the Crusades shaped the dynamics of Christian-Islamic relations that continue to resonate in world history until the modern era.